Conformational properties of interacting neurofilaments: Monte Carlo simulations of cylindrically grafted apposing neurofilament brushes - Jayanthi, Lakshmi (Springer Netherlands, 2012)
Neurofilaments are essential cytoskeletal filaments that impart mechanical stability to axons. They are mostly assembled from three neurofilament proteins that form the core of the filament and its sidearms. Adjacent neurofilaments interact with each other through their apposing sidearms and attain unique conformations depending on the ionic condition, phosphorylation state, and interfilament separations. To understand the conformational properties of apposing sidearms under various conditions and gain insight into interfilament interactions, we performed Monte Carlo simulations of neurofilament pairs. We employed a sequence-based coarse-grained model of apposing NF sidearms that are end-tethered to cylindrical geometries according to the stoichiometry of the three neurofilament subunits. Monte Carlo simulations were conducted under different conditions such as phosphorylation state, ionic condition, and interfilament separations. Under salt-free conditions, apposing sidearms are found to adopt mutually excluding stretched but bent away conformations that are reminiscent of a repulsive type of interaction. Under physiological conditions, apposing sidearms are found to be in a coiled conformation, suggesting a short-range steric repulsive type of interaction. Increased sidearm mutual interpenetration and a simultaneous decrease in the individual brush heights were observed as the interfilament separation was reduced from 60 to 40 nm. The observed conformations suggest entropic interaction as a likely mechanism for sidearm-mediated interfilament interactions under physiological conditions. Electronic supplementary material The online version of this article (doi:10.1007/s10867-012-9293-5) contains supplementary material, which is available to authorized users.